Performance and Behavior of Family Firms - Esra Memili (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Family involvement characterizes a large number of firms around the world and is thought to significantly impact their strategies, behavior, and performance. Family involvement occurs when a family exerts control over the firm through ownership and management. When family involvement leads to intentions to pursue particularistic goals and strategies, controlling families are more likely to exert a significant influence on firm strategies, behavior, and performance. Indeed, intentions imply that a firm's strategic behaviors will be oriented toward preserving the economic and socioemotional value of the firm for the family in the long term. Hence, the "essence" of a family firm is thought to be a function of a family's influence on the culture, functioning, and behavior of the firm owing to the pursuit of a family's vision for the firm. As a result, family firm behavior is expected to be distinct from those in non-family firms. Despite the inherent differences between family and non-family firms and heterogeneity among family firms, family involvement is under-researched in organizational studies, which limits the generalization of findings and leads to theoretical ambiguity. Financial strategic decisions and activities may be key to understanding differences between family and non-family firms. Therefore, we invited researchers to shed light on how a family uses its influence to affect financial strategies, behavior, and firm performance.